THE FUNCTIONAL SIGNIFICANCE OF RECITING DHIKR AL-MA’THURAT: EXPLORING THE LIVING QUR’AN IN TAHFIZ INSTITUTION - Pitriyani, Pitriyani; Sartika, Ela; Ningsih, Indria (Universitas Nurul Jadid, 2024)
This research is motivated by the many practices of reciting the dhikr of Al-Ma’tsurat among institutions both formal and non-formal as a form of spiritual improvement of its readers including at LTIQ As-Syifa Subang, West Java, Indonesia. Therefore, this study aims to explore the functional meaning of the recitation of the dhikr of Al-Ma’thurat and how this practice supports the moral, disciplinary, and mental development of tahfiz students in daily life. This type of research is qualitative with descriptive-analytical method and living Qur’an approach. Data were obtained through observation, interviews, and documentation. The research subjects included santri, musyrifah, and dormitory supervisors. The results showed that the recitation of Surah Al-Ma’thurat at LTIQ As-Syifa is carried out regularly, both daily and certain events organized by the foundation. This activity has a functional meaning that is felt by the readers of the dhikr at LTIQ As-Syifa. First, strengthening the mentality of students, especially in memorizing the Qur’an. Second, reminding oneself to Allah. Third, increasing discipline in worship. fourth, as a form of protection to Allah. Fifth, a means of improving the quality of relationship with Allah. Sixth, a means of shaping the character of students and increasing the spirit of memorization. last, to foster a sense of responsibility for the knowledge possessed while studying at the institution.